Methods of Presenting the Character in the International Prize for Fiction 2018-2020 - Hersh Mohammed Amin; Ihsan Burhanadden Ameen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This research, titled “Methods of Presenting the Character in the International Prize for Fiction 2018-2020” is concerned with studying the ways of presenting the character in three of the novels that received that awards. Based on their release date, they are The Second Dog War by Ibrahim Nasrallah, The Night Post by Hoda Barakat, and The Spartan Diwan by Abd al-Wahhab al-Issawi. The paper starts with character analysis and makes use of some other theoretical frameworks, mainly psycho analysis and stylistics: psychostylistics. Other frameworks such as philosophy and sociology are used a prelude to moving on to the ways in which narrative characters are presented. The characters are presented based on two different levels. One is through the narrator describing them. The other is through readers paying attention to their dialogues and actions.